2021
DOI: 10.21203/rs.3.rs-652594/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rifampicin-resistance Pattern of Mycobacterium Tuberculosis and Associated Risk Factors Among Presumptive Pulmonary and Extra Pulmonary Tuberculosis Patients at Madda Walabu University Goba Referral Hospital, Southeast Ethiopia

Abstract: Background: Drug resistant M.tuberculosis is one of the serious public health trouble that intimidating progress made in tuberculosis cases and control in several countries. Early detection of drug-resistant tuberculosis is crucial for patient management and infection control. Methods: Hospital based cross-sectional study design was conducted from October 2020 to February 2021. Detection of Mycobacterium tuberculosis and resistance to Rifampicin pattern was determined by using GeneXpert MTB/RIF assay. Data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
2
1
0
Order By: Relevance
“…The frequency of EPTB (MTBC) according to the Xpert MTB/RIF assay was consistent with studies conducted in Morocco (20.6%), and findings from Goba, southeast Ethiopia (15.3%) [ 12 , 13 ]. Our findings showed that the prevalence of MTBC was lower than in studies conducted in Dessie (23.4%), Gondar (26.2%), and Addis Ababa (49.3%) [14] , [15] , [16] .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The frequency of EPTB (MTBC) according to the Xpert MTB/RIF assay was consistent with studies conducted in Morocco (20.6%), and findings from Goba, southeast Ethiopia (15.3%) [ 12 , 13 ]. Our findings showed that the prevalence of MTBC was lower than in studies conducted in Dessie (23.4%), Gondar (26.2%), and Addis Ababa (49.3%) [14] , [15] , [16] .…”
Section: Discussionsupporting
confidence: 85%
“…The presence of contact history with known TB patients increased the chance of becoming diseased to four times more than for those who had no contact history. This finding was supported by studies conducted in Goba and Gondar [ 13 , 15 ]. In our study, TBL was the most common confirmed type of EPTB (71.1%).…”
Section: Discussionsupporting
confidence: 76%
“…In December 2010, the World Health Organization (WHO) approved Xpert MTB/RIF (Cepheid, Sunnyvale, CA, USA). This automated molecular system detects both MTB and rifampicin-resistant (RR) tuberculosis concurrently to address the issue of early TB diagnosis in low-income countries ( 7 ). In over 90% of cases, RR-MTB is a surrogate marker for MDR-TB.…”
Section: Introductionmentioning
confidence: 99%